Exploring cyclohexane/piperazine-urea motifs for spherical halide (X = Cl−/Br−) recognition: effects on anion coordination, photoluminescence, and morphological tunability. Issue 44 (28th October 2021) - Basak, Megha; Das, Asesh; Das, Gopal
Abstract : Two bis-urea receptors bearing aromatic meta-substituted electron-withdrawing groups demonstrated halide-coordination-triggered self-assemblies with contrasting coordination numbers and variation in morphology. Abstract : Numerous approaches to receptor fabrication have been introduced for supramolecular anion recognition, not only for academic purposes but also for their substantial application in environmental and biological fields. We highlight halide (X = Cl − /Br − ) coordination-triggered self-assembly formation using two dipodal receptors, L 1 and L 2 . This approach involves several non-covalent interactions, such as N–Hurea ⋯X, C–Hphenyl ⋯X, and C–H n -TBA ⋯X. Structural aspects of the anion-coordinated supramolecular architectures of L 1 and L 2 (1a, 1b, 2a, 2b ) revealed 2 : 1 anion-receptor assembly formation in almost identical fashion, possessing different coordination numbers. Receptor L 1 is composed of cyclohexane-urea motifs, whereas L 2 comprised a piperazine-urea scaffold connected via a propyl spacer, which might be the backbone of the contrasting coordination number of the isostructural anionic ensembles. Solution-state 1 H-NMR and photoluminescence studies corroborated the efficient encapsulation of chloride/bromide via hydrogen bonding interactions. FESEM studies depicted the variations in morphologies in the anion-recognition-triggered self-assembly of the receptors.